1981
DOI: 10.1002/mus.880040304
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial in duchenne dystrophy. I. The design of the protocol

Abstract: Therapeutic trials in muscular dystrophy have often been inconclusive. A protocol has been designed which selects patients with Duchenne muscular dystrophy and permits accurate measurement of their status. An integral part of the protocol is a system for checking on the consistency of the data obtained using a computer program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
311
0
26

Year Published

1982
1982
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 498 publications
(337 citation statements)
references
References 6 publications
0
311
0
26
Order By: Relevance
“…Functional measures developed specifically for older patients with neuromuscular diseases have included the Vignos lower extremity classification scale [16], the Brooke upper extremity scale [17,18], various timed functional assessments [17], and The Hammersmith motor ability scale [19]. More recently the EK scale [20] was developed for non-ambulatory patients with Duchenne's muscular dystrophy (DMD) and SMA, the Wee Fim was utilized to quantify function in children with SMA in Hong Kong [11] and the functional research scale for ALS (FRS-ALS) scale was utilized in clinical trials with adult patients with ALS [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Functional measures developed specifically for older patients with neuromuscular diseases have included the Vignos lower extremity classification scale [16], the Brooke upper extremity scale [17,18], various timed functional assessments [17], and The Hammersmith motor ability scale [19]. More recently the EK scale [20] was developed for non-ambulatory patients with Duchenne's muscular dystrophy (DMD) and SMA, the Wee Fim was utilized to quantify function in children with SMA in Hong Kong [11] and the functional research scale for ALS (FRS-ALS) scale was utilized in clinical trials with adult patients with ALS [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the relevance of motor function follow up to monitor DMD accurately 2,3,4 . Global motor scales should be complemented by functional tasks assessment because, despite the continued decline in muscle strength, children with DMD continue to perform the activities using compensatory movements 5,6 .…”
mentioning
confidence: 99%
“…(i) Semi-quantitative measurements (manual testing, timed scores during motor acts) are performed in routine clinical practice and afford a functional evaluation (Edwards & Hide, 1977;Brooke et al 1981;Aitkens et al 1989). For instance, manual testing (scored from 0 to 5) is based on an international graduated scale of muscle ability: MRC scale (Medical Research Council, 1943) reorganized from 0 to 10 (Brooke et al 1981).…”
mentioning
confidence: 99%